Cytostatic effect of 9-(2-phosphonomethoxyethyl) adenine (PMEA). I. Lymphatic leukemia KHP-Lw-I in Lewis rats - Otová, B; Sladká, M; Votruba, I; Holý, A; Kren, V (Folia biologica, 1993)
PMEA was administered i.p. daily on 10 consecutive days to inbred LEW rats inoculated with leukemic lymphoblastic cells KPH-Lw-I. The treatment was started 24 h after the inoculation. The observed cytostatic effects consisted in a significant prolongation of survival time associated with a suppression of the number of bone marrow leukemia cells with characteristic chromosomal marker of KPH-Lw-I leukemia as well as with a depression of the number of lymphoblasts in the blood.
Keywords: Rats, Inbred Lew; Leukemia, Lymphoid; adenin; experimentální leukemie; krysa rodu Rattus; potkani inbrední LEW; lymfoidní leukemie; Male; Organophosphonates; Animals; protinádorové látky; mužské pohlaví; Adenine; Leukemia, Experimental; organofosfonáty; zvířata; Antineoplastic Agents; Rats